Carbon Dioxide Emissions, Urbanization and Population: Empirical Evidence in Sub Saharan Africa - Adusah-Poku, Frank (Energy Economics Letters, 2016)
Urbanization and population have been viewed as two of the major contributors to global CO2 emissions. This paper aims at examining empirically the relationship between urbanization, population and CO2 emissions in 45 Sub-Saharan African (SSA) countries. This goal was achieved by using a panel data from 1990-2010 and the newly established pooled mean group (PMG) estimator for dynamic heterogeneous panels. This study is a contribution to the empirics of climate change which has been an ongoing debate over the past decades now. The study establishes that an increase in both urbanization and population significantly increases CO2 emissions both in the long and short run. Furthermore, the study finds that, CO2 emissions of countries with large population like Nigeria and Ethiopia tend to grow faster following energy consumption as compared to countries with small population like Cape Verde and Equatorial Guinea.